Development of robust ultra-high-performance carbon nanofiber aggregates (UHPCNFAs) for structural health monitoring. (15th March 2023) - Joshi, Bhagirath; Wang, Jiaji; Li, Xiaoliang; Ramaswamy, Nagesh H; Shrestha, Priyanka; Shan, Xiaonan; Mo, Y.L.; Hsu, Thomas T.C.
Highlights: Ultra-high-performance carbon nanofiber aggreagate is proposed and developed. The relationship between electrical response and stress–strain response are obtained. The influence of scaning frequency and loading orientation are investigated. The proposed sensor has compressive strength of 138 MPa to fit UHPC strength. Abstract: Ultra-high-performance concrete (UHPC) is rapidly implemented to build robust, durable, and sustainable structures. This study presents the development of a robust self-sensing sensor with the motivation to monitor structures with high-performance construction material, such as UHPC. The ultra-high-performance carbon nanofiber aggregates (UHPCNFAs) are carbon nanofibers (CNFs) and UHPC-based smart aggregates. The newly developed UHPCNFAs are experimentally investigated in uniaxial compression. Sweep-frequency and fixed-frequency tests are adopted in alternating current measurements for determining the electrical behavior of the UHPCNFAs. UHPCNFAs are compressed in parallel and perpendicular loading orientations to understand the difference in the sensor's electrical sensitivity and mechanical behavior in each case. In addition, the robustness of the UHPCFNA is examined to the point of failure in both orientations. The relationship between stress, strain, and electrical impedance variation is established for eight different frequencies. Furthermore, the UHPCNFAs are compressed at a fixed frequency to verify the repeatable behavior. This paper examines the effect of loading orientations on electrical and mechanical response, robustness, and sensitivity of UHPCNFA in a wide range of frequency spectrum to check its suitability in real-time structural health monitoring.